Cancer Therapy: Esterase‐Activated Charge‐Reversal Polymer for Fibroblast‐Exempt Cancer Gene Therapy (Adv. Mater. 48/2016). Issue 48 (21st December 2016) - Qiu, Nasha; Liu, Xiangrui; Zhong, Yin; Zhou, Zhuxian; Piao, Ying; Miao, Lei; Zhang, Qianzhi; Tang, Jianbin; Huang, Leaf; Shen, Youqing
Abstract : An esterase‐responsive positive‐to‐negative charge‐reversal polymer is developed for selective gene expression among tumor cells via differentiated dissociation of polyplexes by their intracellular esterase activities, such that TRAIL suicide gene is highly expressed in cancer cells, inducing cancer cell death, but not expressed in fibroblasts. This pacifies them not to secrete the tumor growth and metastasis signal WNT16B, giving rise to potent therapeutic efficacy, as described by Y. Shen and co‐workers on page 10613.